Institutional implementation of orcid identifiers: a new role for university libraries - De-Castro, Pablo (Anuario ThinkEPI, 2015)
It is suggested that university librarians should collaborate in the correct implementation of orcid (Open Researcher and Contributor ID) author identifiers. There is a danger of duplicating the orcids when a university decides to implement a mass registration of its researchers. Librarians have a complex and valuable field of action, giving advice to researchers about signature formats and the characteristics and advantages of orcid identifiers.